2021
DOI: 10.3389/fpsyt.2021.653229
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi on the Executive Function and Physical Fitness of Female Methamphetamine Dependents: A Randomized Controlled Trial

Abstract: Purpose: Exercise improves the health and mental status of drug dependents. The way by which Tai Chi (TC) as a special exercise treatment affects executive functions (EFs) of methamphetamine (MA) dependents is yet to be established. This study aimed to explore the effects of TC on the EFs and physical fitness of MA dependents.Methods: A total of 76 female MA dependents were randomly assigned to the exercise and control groups. The exercise group underwent three 60-min sessions of TC training per week for 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 105 publications
2
8
0
Order By: Relevance
“…The results of shortened incongruent post-test Stroop color-naming test response time in Tai Chi are in line with those of previous studies on the effectiveness of Tai Chi on elderly individuals [ 69 ], methamphetamine dependents [ 70 ], and individuals with mild cognitive impairment [ 71 ]. However, our study expanded to patients with depression, to examine whether the three-month Tai Chi intervention effectively improved the inhibitory control of adults with depression.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of shortened incongruent post-test Stroop color-naming test response time in Tai Chi are in line with those of previous studies on the effectiveness of Tai Chi on elderly individuals [ 69 ], methamphetamine dependents [ 70 ], and individuals with mild cognitive impairment [ 71 ]. However, our study expanded to patients with depression, to examine whether the three-month Tai Chi intervention effectively improved the inhibitory control of adults with depression.…”
Section: Discussionsupporting
confidence: 89%
“…In line with previous studies on otherwise healthy adults [85], elderly individuals [86], and methamphetamine-dependent women [70], this study demonstrated that the Tai Chi intervention comprehensively improved the physical fitness of adults with depression. us, Tai Chi was found to be conducive to improving an individual's cardiovascular fitness, muscle strength, muscle endurance, power, and flexibility.…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 90%
See 1 more Smart Citation
“…To test whether the sample size of ANOVA is reasonable, G*power 3.1 (Franz faul, Universitat Kiel, Germany) was used to conduct the post hoc statistical power analysis. Referring to the parameter settings in previous study ( Menglu et al, 2021 ), the ANOVA test was selected, the effect size was set as 0.23, the significance level as 0.05, the sample size as 47, the number of groups as 2, and the number of repeated measurements as 6, the calculated power value was 0.99, exceeding the basic level by 0.80. Therefore, the sample size of this study complied with the requirements.…”
Section: Methodsmentioning
confidence: 99%
“…Different types of intervention, aimed at improving cognitive functioning of methamphetamine users, have recently been examined. These include electrical brain stimulation (e.g., Alizadehgoradel et al, 2020 ), various types of physical exercise ( Liu et al, 2021 , Menglu et al, 2021 , Qi et al, 2021 ), and cognitive trainings ( Bickel et al, 2011 , Brooks et al, 2016 ). The first two types of intervention are promising, but require more systematic research on training parameters and possible modulators of training effects in terms of, for example, duration of drug use and abstinence.…”
Section: Introductionmentioning
confidence: 99%